The Effect of Project-Based Learning on Creativity and Learning Outcomes in Mixture Separation - Hesti Wulandari; Eny Enawaty; Andi Ifriani (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2026)
Students’ learning outcomes and creativity remain suboptimal despite the implementation of the Merdeka Curriculum. This study investigated the effect of Project-Based Learning (PjBL) on students’ creativity and learning outcomes in mixture separation at SMP Negeri 8 Pontianak. A pre-experimental one-group pretest–posttest design was employed with 36 eighth-grade students selected through purposive sampling. Data were collected using learning outcome tests, a creativity rubric based on Guilford’s dimensions (fluency, flexibility, originality, and elaboration), documentation, and semi-structured interviews. The Wilcoxon Signed-Rank Test was used for data analysis. The findings revealed statistically significant improvements in learning outcomes (Z = –5.110; p < 0.001) and creativity (Z = –5.214; p < 0.001), accompanied by very large effect sizes. These results highlight the substantial contribution of PjBL in fostering students’ creativity and academic achievement and reinforce its relevance as an effective instructional approach within the framework of the Merdeka Curriculum.